Pengaruh Fasilitas Akses Jalan Masuk Terminal Terhadap Kepuasan Penumpang di Bandar Udara Tebelian Sintang Kalimantan Barat - Wahyu Saputro; Djoko Widagdo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The high demand for air transportation services, more adequate facilities and the rapidly growing number of passengers are the background of research on the effect of terminal access access facilities on passenger satisfaction at Tebelian Sintang airport, West Kalimantan. This study aims to determine how much influence the terminal entrance access facilities have on passenger satisfaction at Tebelian Sintang Airport, West Kalimantan. The data for this study were collected from the Journal Report Station 2010 - 2021 at Tebelian Sintang Airport and distributed questionnaires to 100 respondents using a closed questionnaire. The results of the analysis show that the effect of the availability of road access facilities on passenger satisfaction is 71.4% which has a very high influence and the remaining 28.6% is influenced by other variables not included in this study.